Find \( f(g(x)) \) and \( g(f(x)) \) and determine whether the pair of functions \( f \) and \( g \) are inverses of each other. \( f(x)=4 x+2 \) and \( g(x)=\frac{x-2}{4} \) a. \( f(g(x))=\square \) (Simplify your answer.)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To find \( f(g(x)) \), we first substitute \( g(x) \) into \( f(x) \): \[ g(x) = \frac{x-2}{4} \] Now, substituting \( g(x) \) into \( f(x) \): \[ f(g(x)) = f\left(\frac{x-2}{4}\right) = 4\left(\frac{x-2}{4}\right) + 2 \] When we simplify this: \[ f(g(x)) = (x-2) + 2 = x \] So, we have: \[ f(g(x)) = x \] Now, let’s find \( g(f(x)) \): First, we substitute \( f(x) \) into \( g(x) \): \[ f(x) = 4x + 2 \] Now substituting \( f(x) \) into \( g(x) \): \[ g(f(x)) = g(4x + 2) = \frac{(4x + 2) - 2}{4} \] Simplifying this gives: \[ g(f(x)) = \frac{4x}{4} = x \] So, we have: \[ g(f(x)) = x \] Since both \( f(g(x)) = x \) and \( g(f(x)) = x \), the functions \( f \) and \( g \) are indeed inverses of each other.